Pembelajaran al-Quran Menggunakan Pendekatan Ilmiah di SMPN 1 Kadipaten Tasikmalaya - Nasir, Tatang Muh; Irawan, Irawan; Priyatna, Tedi (Tarbawiyah Jurnal Ilmiah Pendidikan, 2022)
This paper aims to describe the implementation of Islamic learning with a scientific approach to learning materials for reading the Koran in high school. The method used in this research is qualitative. Data were collected using document study techniques, interviews, and observations. The results of the study show that in several theoretical aspects of learning, scientific principles have been used because 1) it has included the process of observing, asking questions, gathering information, associating, and communicating; 2) have used several standardized Qur'anic learning methods and through the results of trials or research. The combination of the use of scientific principles and some of the results of trials of the Qur'anic learning method can strengthen the quality of scientific Qur'anic learning and the assessment of learning outcomes becomes more measurable.